Perceived inclusion and team creativity climate: examining the role of learning climate and task interdependency. Issue 6 (8th December 2020) - Ghosh, Vinit; Tripathi, Nachiketa
Abstract : Purpose: This paper aims to investigate the relationship between perceived inclusion (individual and group-level) and team creativity climate (TCC) and explore the role of team learning climate (TLC) and task interdependency in the above relationship. Design/methodology/approach: Data were collected using questionnaires from 24 Indian organizations. The respondents were junior and middle-level employees ( N = 303) working in small teams ( n = 73). The cut-off criteria for sample team selection were at least three team members within a team had responded and at least 60% within-group response rate was achieved. Findings: Perceived inclusion (PI) of employees had a positive influence on TCC via TLC. However, the negative effect of team-level differences in perceived inclusion (TPID) was also mediated by the learning climate. Task interdependency moderated the PI-TLC relationship in such a way that in a high task interdependency situation, the negative effect of TPID on learning climate is reduced, while in a low task interdependency situation, the negative effect is enhanced. Originality/value: The current research has contributed to the limited literature on PI and team creativity. This paper has uniquely investigated TLC as an intervening variable in the PI-TCC relationship. The paper has encapsulated the theoretical and practical underpinnings of inclusion beliefs in the modern organizational context.